“Visible invisibility”: from traditional ṭaggāgāt to Samra female pop stars, representations and performativity of race and gender in the northern Arabian Peninsula - Coline Houssais (Arabian Humanities)
This article looks at how race and gender are represented and performed as far as female Sumr (brown skinned) performers in the northern Arabian Peninsula are concerned, from traditional ṭaggāgāt (wedding singers) to contemporary pop stars. Its main thesis is that musical entertainment over the centuries has been conducted by Sumr on the basis that it was not deemed suitable by the cultural orthodoxy of the time, and that therefore only individuals and communities located at the margins of society, such as the Sumr then, could be associated with it. By doing so their position within northern Arabian societies became one of integrated marginality, and, when the repertoire performed predominantly by Sumr became a key element of the patrimonialization of cultural heritage in the context of national identities definition conducted by newly independent states, they became the object of visible invisibility. A phenomenon that exists to this day, including in other spheres of the music industry.